Intracholecystic papillary-tubular neoplasm in a patient with choledochal cyst: a link between choledochal cyst and gallbladder cancer? - Michalinos, Adamantios (World J Surg Oncol, 2016)
BACKGROUND: Intracholecystic papillary-tubular neoplasms are rare precursor lesions of gallbladder cancer. They were proposed as a separate pathologic entity in 2012 by Adsay et al. for the unification of a variety of mass-forming precursor lesions including papillary adenomas, tubulopapillary adenomas, intestinal adenomas, and others. They are considered homologous to intrapapillary mucinous neoplasms of the pancreas and intrabiliary papillary neoplasms of the common bile duct. In contrast with the commoner flat-type precursor gallbladder cancer lesions, they follow a more indolent clinical course and probably different genetic pathways to carcinogenesis. They are largely uninvestigated with only a handful of studies providing biological and clinical information. Choledochal cysts are dilation of the common bile duct. Diagnosis is usually established during childhood, and only a minority of patients are diagnosed at adulthood. They are of major clinical importance as they are known predisposing factors for biliary carcinogenesis. CASE PRESENTATION: The current report describes a patient with a simultaneous diagnosis of choledochal cyst and intracholecystic papillary-tubular neoplasm. The patient underwent excision of the extrahepatic biliary tree for a Todani I choledochal cyst, and histological examination of the specimen revealed an intracholecystic papillary-tubular neoplasm of the gallbladder. Authors describe diagnostic and clinical course of the patient alongside clinical and biological characteristics of these rare lesions. CONCLUSIONS: To the best of our knowledge, this is the first report of a patient with a simultaneous diagnosis of choledochal cyst and intracholecystic papillary-tubular neoplasm. Those rare lesions shed light on different forms of gallbladder cancer carcinogenesis and its relationship with choledochal cysts and cholestasis.